Evaluating the effectiveness of Thiel embalming solution for preserving cadavers in anatomy and surgical education - Indrawan, I Made Rayo Putra; Margiana, Ria (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2025)
Cadavers have played a crucial role in anatomy teaching, owing to their resemblance to the anatomical structures found in living individuals. To optimize the utilization of cadavers, embalming procedures that involve the application of chemical fixative agents are needed. The "soft embalming" approach, which involves various salts as fixating agents, was first developed by Walter Thiel. Although the Thiel solution has demonstrated efficacy in enhancing tissue elasticity, consistency, and color, a study is needed to find the most suitable for embalming with this solution to maximize its utility in the context of anatomy and surgical education. The study results show that the Thiel solution produces the best outcomes for its flexibility, uniformity, and color, which is optimal for anatomical and surgical teaching. The efficacy of Thiel's solution for preserving cadavers for educational intentions is noteworthy for the study of anatomy and surgical procedures. The advantageous characteristics of Thiel embalming include flexibility, consistency, and natural coloring. Nevertheless, it is crucial to consider the restrictions associated with preserving the brain, spinal cord, eye, and musculoskeletal tissues. In conclusion, the utilization of Thiel solution has proven to be an efficient embalming agent for preserving cadavers in the fields of anatomy and surgery education, besides brain, spinal cord, eye, and musculoskeletal systems, should be reconsidered.